2018
DOI: 10.1177/1933719118804404
|View full text |Cite
|
Sign up to set email alerts
|

The Link Between Seminal Cytokine Interleukin 18, Female Circulating Regulatory T Cells, and IVF/ICSI Success

Abstract: Seminal plasma (SP) is thought to be a crucial factor which affects the expansion of regulatory T cells (Tregs) in female reproductive tract during embryo implantation. We propose that seminal transforming growth factor (TGF) β1 is responsible for local accumulation of circulating Tregs, which manifests as changes in Treg frequency in peripheral blood, whereas seminal interleukin (IL) 18 interferes with TGF-β1-dependent cellular reactions. The purpose of the present study is to determine whether the frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…According to modern concepts, the migration of immunocompetent blood cells makes a significant contribution to the formation of a preimplantation immune profile of the endometrium 58. Indeed, in our previous work we have shown that increased frequency of regulatory T cells in female peripheral blood could be the marker of pregnancy failure in IVF/ICSI-treated patients 59. Here, we revealed that increased level of CD200 expression is also associated with an increase in the percentage of regulatory T cells in female peripheral blood in the non-pregnant group (compared with women who became pregnant after LIT).…”
mentioning
confidence: 93%
“…According to modern concepts, the migration of immunocompetent blood cells makes a significant contribution to the formation of a preimplantation immune profile of the endometrium 58. Indeed, in our previous work we have shown that increased frequency of regulatory T cells in female peripheral blood could be the marker of pregnancy failure in IVF/ICSI-treated patients 59. Here, we revealed that increased level of CD200 expression is also associated with an increase in the percentage of regulatory T cells in female peripheral blood in the non-pregnant group (compared with women who became pregnant after LIT).…”
mentioning
confidence: 93%